The role of endowments and behaviours in street trader upliftment within the City of Johannesburg - Volker, Cordelia (My University, 2019)
The purpose of the study was to investigate the importance of endowments versus behaviours in relation to street traders within the inner city of Johannesburg, Gauteng. Street traders form an integral part of urban economics and as such are one of the most visible occupations, yet few cities successfully balance the need to support livelihoods with the need to manage public space. Street traders can be viewed as a highly vulnerable group. The knowledge problem addressed in this research is the lack of knowledge of the contribution of endowment and behaviour attributes to the performance of street traders. Such knowledge is considered particularly important in the wake of events, such as Operation Clean Sweep, that may have had a lasting influence on the experience of street traders, and their ability to earn their livelihoods. Whereas behavioural theory such as the entrepreneurship orientation theoretical framework predicts that certain behavioural characteristics of an individual, namely risk taking, proactiveness, innovativeness, competitive aggressive and autonomy can contribute in different ways to performance across different contexts. Sustainable livelihood theory highlights the importance of endowments, taken here to be representative of Bourdieu’s forms of capital, in achieving a sustainable livelihood. While the interactive contributions of these theoretical contributions on performance seem to exist across many entrepreneurial contexts, it is not clear according to these bodies of theory which of these approaches is most effective in the context of inner-city street trading. More specifically, it is not clear whether behavioural theory predicts the behaviour of the lowest-earning street traders in the sector, or whether their life chances are, instead, dictated by their lack of endowments of financial or social capital. Drawing from the entrepreneurship orientation and sustainable livelihood theoretical frameworks, a qualitative study of 20 low earning inner-city Johannesburg street traders was undertaken to investigate certain tensions between the predictions of these bodies of theory. The data was analysed using thematic analysis. Such knowledge is important to gain an understanding of the types of interventions needed to uplift street traders. If endowments, such as access to resources, either in the form of financial capital or social capital, are a necessary condition for street trader upliftment then certain assumptions in the street trader literature may need to be revisited. Findings question assumptions about the ability of low-earning inner-city street traders to transcend endowment constraints in this context. If behavioural attributes are not sufficient to transcend a threshold limitation associated with endowments, then certain predictions of entrepreneurial theory might not be iii valid for certain individuals in this context. The research concludes that certain inner-city street traders have limited agency. The implication of this is that their ability to improve their livelihoods through behavioural change is limited. Although both behaviours and endowments are important for street traders to achieve full functionality as entrepreneurs, the results of this study suggest that a lack of endowments presents a binding constraint to their functionality, and that urgent intervention is necessary to improve their quality of life, and to ensure their earnings are sufficient to maintain their minimum levels of nutrition and health.
A dissertation submitted to the faculty of commerce, law and management, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Master of commerce in management, Johannesburg, South Africa, December 2018